Analysis of Child Rights Violation: Forced Marriage Underage and Collaborative Practice - Ika Purnamasari (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2021)
Children's rights are part of human rights that must be guaranteed, protected and fulfilled by parents, family, community, state, government and local government. This article discussed the analysis of a case of violation of children's rights in the form of forced marriage to a child. The case description is an 11-years old girl forced to marry a 50-years old man. The child was bleeding and frightened and then the child was admitted to a hospital. The question that arises based on the description of the case is